The effect of frog jumping and skipping exercises on squat style long jump results - I Bagus Endrawan; Kusbandi Kusbandi; Martinus martinus (Universitas Suryakancana, 2022)
This study aims to determine the effect of frog jumping and skipping exercises on the results of the long jump squat style of grade VIII students of SMP Negeri 1 Lintang Kanan. The research method in this study is an experimental method. The research design used is the modified pre-test – post-test group design. The data collection technique in the study used the long jump test. The results of the study on the significance of the pre-test and post-test of frog jumping and skipping exercises on the results of long jump and squat class VII of SMP Negeri 1 Lintang Kanan were calculated with a t-test with data criteria said to be significant if the calculation ≥ ttabel. From the calculation results, it is known that the calculation of 10.44 The result was then consulted with a ttable of 1.76 (α = 0.05). It showed that the calculation ≥ ttabel, 10.44 ≥ 1.76 (significant). Meanwhile, the significance level of pre-test and post-test skipping is known that the calculation is 10.58. The results were then consulted with a ttable of 1.76 (α = 0.05) It showed that the calculation of the ≥ ttabel, 10.58 ≥ 1.76 (significant). The effectiveness of frog jumping and skipping exercises is not far apart, namely the frog jumping exercise method is able to increase by 4.84% while skipping is able to increase by 4.54%. Based on these results, it can be stated that there is an effect of the skipping method on the long jump squat style results of class VIII students of SMP Negeri 1 Lintang Kanan.Key words: Leap Frog, Skipping, Long jump